Diversity of disease-carrying mosquito vectors in potential areas of dengue fever in Palembang City, South Sumatra, Indonesia - HERU LISTIONO; NURHAYATI DAMIRI; TOTONG KAMALUDDIN; CHANDRA IRSAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Listiono H, Damiri N, Kamaluddin T, Irsan C. 2024. Diversity of disease-carrying mosquito vectors in potential areas of dengue fever in Palembang City, South Sumatra, Indonesia. Biodiversitas 25: 474-481. Mosquitoes (Diptera: Culicidae) are biting insects commonly found in many areas on earth in subtropics and tropics, especially around residential areas. So far, more than 2500 species have been recorded from various parts of the world. They are the main vectors of many diseases in humans and livestock caused by viruses and parasites. Mosquito diversity and disease transmission are influenced by landscape modifications, namely vectors and pathogens. The study aimed to evaluate the distribution, prevalence and abundance of mosquito species in potential dengue fever districts in Palembang city. The study was conducted in 2 two sub-districts in Palembang City, namely Gandus and Seberang Ulu I that represent housing environment, schools and gardens. Mosquito capture was done during three periods 06.00-10.00, 15.00-18.00, and 19.00-21.00 to align with their active hours. This involved active human landing collection method. 200 ovitraps were set up in both regions to assess the density of mosquitoes. The results showed that the diversity index values in Gandus and the Seberang Ulu I sub-districts were 0.781 and 0.756, respectively. Both values were categorized as low diversity index. Furthermore, the dominance index in Gandus and Seberang Ulu 1 sub-district were 0.105 and 0.031, respectively. It meant that there were no dominant mosquito species in both sub-districts. Based on the results of Independent t-test analysis, it was found that the average number of mosquito populations in Gandus sub-district was 25.07 and Seberang Ulu I sub-district was 13.29. From the results of the analysis it was found that there was no difference in average number of mosquito populations between Gandus and Seberang Ulu I sub-district, with a p-value of 0.367. Further research needs to be directed at uncovering mosquito distribution patterns and their potential as disease vectors, the risk of infectious diseases, and the need for further prevention to reduce the number of disease incidences.